(untitled) - Bhattacharyya, Shankar P (Englewood Cliffs, New Jersey, 1995)
This book describes the parametric theory in a self-contained manner. The entire development is based on the single fundamental fact that the roots of a polynomial depend continuously on its coefficients. Topics inculude: Background and motivation; stability theory via the boundary crossing theorem; stability of a line segment; the stability ball in coefficient space; the parametric stability margin; interval polynomials: Kharitonov's theorem; the edge theorem; the generalized Kharitonov theorem; frequency domain properties of linear interval systems; robust stability and performance under mixed perturbations; multilinear interval systems: the mapping theorem; state space parameter perturbations; robust parametric stabilization; interval modelling, identification, and control
Keywords: automatic control